Experimental studies of latent heat storage based solar air heater for space heating: A comparative analysis. (15th June 2023) - Saxena, Abhishek; Cuce, Erdem; Singh, Desh Bandhu; Sethi, Muneesh; Cuce, Pinar Mert; Sagade, Atul A.; Kumar, Avnish
Abstract: There are numerous applications of solar energy technology, among which an air heating system is commonly used for space heating, wood seasoning, industrial drying, etc. Previous research focuses on the bulk usage of different latent heat storages, which is a costly method for performance improvement, especially for solar heating systems. Another major problem with bulk energy storage is that it takes a long time to be charged completely, which results in low-rate air heating at the start. The present research focuses on an economical solution for solar air heating, especially under India's mild cold climatic conditions. About 36 tiny cylindrical containers have been used to carry the two low-cost phase change materials (PCMs), i.e., coconut oil and paraffin wax. These materials have been filled inside the small containers and placed over the solar absorbers of modified models of air heaters, namely, SAHS-2 (with coconut oil) and SAHS-3 (with paraffin). A total of 02 configurations have been developed to conduct the air heating trials on natural and forced convection. To the best of the author's knowledge, likely methodology has not been applied to any air heating system to improve performance for extended hours, especially in a cold climate. Results have been compared with the same size conventional solar heater (SAHS-1) and some other relevant designs of SAHS to observe the significance of PCMs and their appropriateness for air heating. Finally, the model SAHS-3 is found to be the best-configured air heater, capable of performing efficiently under mild cold climates. Experimental studies showed that the best model provides enhanced heat transfer of about 372.81 W/m 2 K, thermal efficiency of about 75.9%, a heat loss coefficient of about 4.93 W/m 2 K, and outlet air temperature of about 44.07 °C under forced convective operations. The estimated cost of the modified heater is approximately 61, while its payback period is about 4.38 years. Highlights: An economical solar air heating system is designed and fabricated for space heating. 02 different PCMs are tested (paraffin wax and coconut oil) under the modified air heating systems. The modified systems are capable to provide the hot air under mild cold climate conditions. The best model has the thermal efficiency about 75.90%. The total cost of this model is approximately 61and the payback is about 4.38 years.